A comparison of Thoracic Bioimpedance and Pulse Contour analysis in cardiac output monitoring in critically ill - Ghazali, Abdul Majid; Mat Nor, Mohd Basri; Md Ralib, Azrina (Universiti Kebangsaan Malaysia, 2021)
The latest invention of Thoracic Bioimpedance (TBE) has shown promising results in multiple areas but lacking in the study with gold standard cardiac output monitoring. This study compared cardiac output monitoring between TBE and the latest technology ICG and PiCCO in the critically ill. All patients were in septic shock with a SOFA score of > 4. Cardiac output parameters were taken at four intervals. Parameters taken were CO, CI, SV, SVi, SVR and SVRI. Pearson’s r correlation coefficient showed significant results for SVR with R of R: 0.92 at 1 hour, 0.543 at 6 hour, 0.638 at 12 hour, and 0.551 at 24 hour (P-value of <0.05). There was a moderate correlation of stroke volume r: 0.426 with a P-value <0.005. moderation correlation was seen in stroke volume index at stage 2 (R 0.383), stage 3 (R 0.504) and stage 4 (R 0.411) with stroke volume also showed moderate correlation at stage 3 (R 0.426) and stage 4 (R 0.411), even though both parameters showed no significant correlation. In mean difference, there were significant differences at stages 3 and 4 (p-value <0.05) in stroke volume index, while the Cardiac index only showed significant differences in stage 4. Bland Altman showed a discrepancy result between both tools and the presence of bias. All cardiac output parameters were statistically not significant except SVR. Haemodynamic parameters from Physioflow were not interchangeable with PiCCO.